Willem Goeree (1635-1711) en de ontwikkeling van een algemene architectuurtheorie in de Nederlanden (Bulletin KNOB, 1997)
In his ‘d'Algemene Bouwkunde’ (General Architecture) of 1681 Willem Goeree rightly concluded that in The Netherlands the most general aspects of architecture had hardly been studied, unlike the five orders of architecture. His treatise is in fact the first printed treatise on architecture in the Dutch language in which an attempt was made to find a connection between architecture of classical antiquity and contemporary architecture which surpassed the usual discussions of the columns or the presentation of designs by leading architects such as Post or Vingboons.Moreover, Goeree pointed out to the urban elite that its task did not just consist in embellishing the town with splendid palaces, but also in providing facilities from which all the citizens would benefit. Because of the wide range of themes dealt with and the attention for the public character of architecture ‘d'Algemene Bouwkunde’, more than any other seventeenth-century Dutch architecture treatise, also breathes the atmosphere of Vitruvius's De Architectura Libri Decem. Possibly due to the absence of illustrations this little treatise never attracted the attention received by the Dutch adaptations of the column books. An autograph handwriting of ‘d'Algemene Bouwkunde’, on the other hand, comprises many prints as well as some drawings by Goeree himself.As regards content, too, it is an important addition to the printed version. Because of the dozens of authors who are quoted, from a historiographic point of view the handwriting constitutes one of the major sources of Dutch theory of architecture. It gives a good picture of the reception of international theory of architecture in the Low Countries, in which the attention paid to Scamozzi and to the advantages and disadvantages of the many Dutch adaptations of his treatise is especially striking.Whereas for his discussion of the orders of columns Goeree could make use of many examples, in his treatise on ‘general architecture’, bringing up themes such as the private house, rural buildings, civil-technical constructions, technical and organizational aspects of building, he had far fewer written sources at his disposal.He compensated for this on the one hand by taking an enormous collection of drawings and models as starting-point of his descriptions, on the other hand by using texts on the civil architecture of Simon Stevin and possibly of Nicolaas Goldmann. Goeree's attention for this general ‘civil’ architecture did not only spring from the challenge to present something ‘new’, but it also had to do with a shift in interest from art-historical subjects to religious and church-historical questions.This shift also affected his writings on the theory of architecture, in which the study of the biblical origin of architecture was to get more and more emphasis, with themes such as the temple of Solomon and the tabernacle of Moses. For Goeree both classical Greek and Roman architecture and the architecture without rules and laws produced by man in a process of trial and error, were to be traced back to one and the same divine example.God had appointed man as his sub-architect and Goeree considered it his calling to penetrate this architecture and learn a lesson from it for contemporary building practice. For The Netherlands this was exceptional and it was to take more than a century before another attempt was made to find a link in a broad sense between the architectural form language of elitist Classicism and civil architecture.Since the texts of Stevin were only partly published and the writings composed by Goldmann in Leyden were to be posthumously published in the German language, the theme of civil architecture did not receive the attention it would get in Germany or France. Nevertheless, these works indicate that ‘d'Algemene Bouwkunde’ of Goeree was not an isolated case and that in the Dutch Golden Age a more general theory of architecture was also sought, comprising far more than the correct use of the five orders of architecture.